The characterization of potential solar thermal on the development of solar oven in the Malaysian climate / Zainoor Hailmee Solihin, Noriah Yusof and Wan Sulaiman Wan Mohamad - Solihin, Zainoor Hailmee; Yusof, Noriah; Wan Mohamad, Wan Sulaiman (Research Management Institute (RMI), 2011)
The trend of using solar cooker is very popular in many regions that have good and reliable solar radiation intensity throughout the year.. The reasons are ; it is more economical, as the price of fuel for cooking is no longer affordable by many families; ecological, as in many regions deforestation is also associated with the use of wood as an energy source(Nandwani, 1996); and social, as the money used to buy fuel could be used to buy food, medications and other needs to improve the quality of life(Klemens Schwarzer, 2008). However, the problem of energy cost and its continuous increase made people, not only in remote areas and villages but also in cities, accept the use of alternative energy sources(SAID M. A. IBRAHIM, 1995). Many of the devices such as solar water heaters, solar cookers, solar dryers have been commercialized in different parts of the world(Ishan Purohit 2009). In order to have a sustained growth of the solar energy technologies it is essential to have a proper mechanism for characterizing the performance of these devices and systems under various climatic and operating conditions (Ishan Purohit 2009). Therefore, it is critically important to adopt and implement test procedures and methodologies for producing performance characteristic parameters, which could provide an equitable basis for comparison of performances of the products offered to the end user.